Lernen zwischen freiem und instruiertem Tätigsein - Hildebrandt, Elke; Peschel, Markus; Weißhaupt, Mark (Lernen und Studieren in Lernwerkstätten, 2014)
Starting from an examination of the concept of being active - as a prerequisite for learning processes - this volume discusses the significance of freely chosen versus instructed activities and places them in the contexts of teaching and learning workshop work. The juxtaposition of instructed and free activity challenges us to determine more precisely the relationship between instruction and successful construction in the interaction between learning facilitator and learner. This applies to work in learning and research workshops, in learning labs and in learning in the "normal" seminar room or classroom. All in all, the question arises: Can the activity of discovering, researching, practice-oriented and cross-discipline learning be made one's own in such a way that it becomes habitual learning? And: should it do so at all?